Species Richness of Medicinal Plants in the Dieng Plateau (Universitas Negeri Semarang, 2019)
The Dieng Plateau is an active volcanic area in Central Java, which belongs to the Banjarnegara Regency and Wonosobo Regency. The Dieng Plateau has an abundance natural potency, such as of plants. This study aims to identify the plant species richness and its benefits by local people. The plants species richness data collected by exploration method. Data collection is done by means of exploration, identification, interview, literature, analyzes, and documentation. The results of the study found there are 29 species of medicinal plants originating from 22 families. The plant that is most widely used as a medicine comes from the family Solanaceae, which is Tamarillo (Solanum betaceum Cav.). The most common species of medicinal plants are found in Parikesit Village. The knowledge of the Dieng Javanese people about the benefits of medicinal plants is mostly influenced by generations (73.2%). The most widely used parts of plant organs are the leaves. The processing technology of plants that usually used is by pulverizing. The medicinal plants mostly found in the Dieng Javanese yard. It proves that the medicinal plants is still used by the Dieng Javanese people as knowledge that can be passed on to the next generation.